2003
DOI: 10.1261/rna.5960503
|View full text |Cite
|
Sign up to set email alerts
|

G-quartet-dependent recognition between the FMRP RGG box and RNA

Abstract: Fragile-X syndrome, the most common monogenic form of mental retardation, is caused by down-regulation of the expression of Fragile X Mental Retardation Protein (FMRP). FMRP is a multifunctional, multidomain RNA-binding protein that acts as a translational repressor in neuronal cells. Interaction between FMRP and mRNA targets involves an RGG box, a protein motif commonly thought to mediate unspecific interactions with nucleic acids. Instead, FMRP RGG box has been shown to recognize RNA G-quartet structures spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
115
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 35 publications
(41 reference statements)
6
115
0
Order By: Relevance
“…In accordance with data from our previous study (6), we found that the N terminus of ICP27 is flexible and not well folded. NMR analysis of the RGG box region of FMRP also showed that this region was flexible and unstructured; however, when a Gquartet sequence was present, the FMRP RGG box region became more structured (30). In the case of ICP27, we did not discern any differences in the spectra of the N-terminal protein alone compared to those of the N-terminal protein in the presence of gC sequences to which it binds (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In accordance with data from our previous study (6), we found that the N terminus of ICP27 is flexible and not well folded. NMR analysis of the RGG box region of FMRP also showed that this region was flexible and unstructured; however, when a Gquartet sequence was present, the FMRP RGG box region became more structured (30). In the case of ICP27, we did not discern any differences in the spectra of the N-terminal protein alone compared to those of the N-terminal protein in the presence of gC sequences to which it binds (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Because our previous results showed that the N-terminal 160 amino acids of ICP27 are highly flexible (6), we sought to determine if ICP27 bound to a gC oligonucleotide would confer more rigidity or folding on the N terminus. This was seen in NMR analyses of the cellular protein fragile X mental retardation protein (FMRP) when the RGG box was bound to G-quartet RNA substrates (30). The protein encoding the N-terminal 160 amino acids of ICP27 was expressed in E. coli Rosetta cells in minimal medium containing 15 NH 4 Cl to isotopically label the expressed proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these RNAs harbor motifs that may form G-quartets and G-quadruplexes in vivo (21, 25). Several mRNAs contain regions shown to form G-quadruplexes implicated in FMRP binding in vitro (21,24,(26)(27)(28)(29). Notably, binding of FMRP to G-rich RNAs in vitro requires only the RGG motif, which specifically interacts with natural and in vitro selected G-quadruplex-containing RNAs such as a 35-nucleotide sc1 RNA (21,(26)(27)(28)(29).…”
mentioning
confidence: 99%